2018
DOI: 10.1186/s12935-017-0496-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel Notch1 missense mutation (C1133Y) in the Abruptex domain exhibits enhanced proliferation and invasion in oral squamous cell carcinoma

Abstract: BackgroundNotch1 has been regarded as a fundamental regulator in tissue differentiation and stem cell properties. Recently, Notch1 mutations have been reported intensively both in solid tumors and in hematopoietic malignancies. However, little is known about the biological effect and the clinical implication of these reported mutations. Previously, we discovered several missense mutations in the Notch1 receptor in a Chinese population with oral squamous cell carcinoma (OSCC).MethodsWe selected a ‘hotspot’ muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 56 publications
(62 reference statements)
0
14
1
Order By: Relevance
“…The downstream target Hes1 might directly downregulate expression of PTEN, increasing PI3K activity [155] (Figure 4). In a screening for Notch1 inactivating mutation, the oncogenic phenotype was associated with activation of the EGF-PI3K/AKT pathway and resulted in increased cell proliferation, EMT, and invasion in OSCC cell lines [156].…”
Section: Introductionmentioning
confidence: 99%
“…The downstream target Hes1 might directly downregulate expression of PTEN, increasing PI3K activity [155] (Figure 4). In a screening for Notch1 inactivating mutation, the oncogenic phenotype was associated with activation of the EGF-PI3K/AKT pathway and resulted in increased cell proliferation, EMT, and invasion in OSCC cell lines [156].…”
Section: Introductionmentioning
confidence: 99%
“…As Notch1 has been suggested as a tumor suppressor in several studies ( 23 , 45 , 46 ), it is possible that membranous Notch1 accumulation is simply an alternative mechanism to inactivate the gene function. However, a recent study revealed that the Notch signaling pathway was active in about one third of Caucasian patients with HNSCC ( 34 ), suggesting an oncogenic role of Notch signaling in a significant proportion of patients with HNSCC in both Chinese and Caucasian populations, although the mechanisms of tumorigenesis could be different ( 47 ). Further studies are warranted to determine how membranous Notch1 accumulation leads to oral tumorigenesis and OSCC progression.…”
Section: Discussionmentioning
confidence: 99%
“…Human OSCC cell lines (HN4, HN6, HN13, and CAL27) were provided as previously described 17,30 . HOK cells were purchased from the American Type Culture Collection (ATCC).…”
Section: Tissue Samples and Cell Culturementioning
confidence: 99%
“…Although FBXW7 has been described to be involved in NOTCH1 protein degradation, no literatures have reported the interplay between FBXW7β and mutant NOTCH1 in the Abruptex domain yet. We have previously found that the NOTCH1 C1133Y mutation led to the retention of NOTCH1 protein in the endoplasmic reticulum and reduced the transport of full-length NOTCH1 protein from endoplasmic reticulum to the Golgi apparatus 17 . Matsumoto et al 31,32 reported that FBXW7β includes a supposed transmembrane domain and suggested that it substantially penetrates the ER membrane.…”
Section: Fbxw7β Interacted With Notch1 C1133y In the Endoplasmic Retimentioning
confidence: 99%
See 1 more Smart Citation